Shank3 mutation manifests in abnormal gastrointestinal morphology and function in mice - Eberly, Gari L.; Manthey, Marie; Pang, Karen K. L.; Hussein, Heba; Vargas Paniagua, Emmanuel; Machen, Scott; Klingensmith, Sara Maeve; Anikeeva, Polina (Frontiers in Neuroscience, 2025)
BackgroundGastrointestinal (GI) comorbidities are common among those with Autism Spectrum Disorder (ASD), but their etiology is not well understood. This study aimed to characterize gastrointestinal morphology and function in Shank3B mutant mice, a common genetic model of ASD, to identify potential alterations to the GI tract that could underlie ASD-associated GI comorbidities.MethodsGI and enteric nervous system morphology was characterized using Hematoxylin and Eosin staining and immunohistochemistry. GI permeability was measured using the FITC-Dextran paracellular permeability assay. Whole-GI tract motility time was measured in vivo using the carmine dye motility assay. Colonic contractions were characterized by tracking motility using an ex vivo motility assay.ResultsHomozygous knock-out (KO) Shank3B−/− mice exhibit significantly altered epithelial morphology and increased GI permeability. An increased myenteric plexus density and a higher number of HuC/D-expressing neurons in myenteric ganglia are observed in the colon of Shank3B−/− mice. These mice exhibit slowed whole-GI tract transit and reduced velocity and propagation length of colonic contractions. Compared to Shank3B−/− mice, heterozygous Shank3B+/− mice exhibit milder epithelial, neuronal, and functional alterations.ConclusionShank3B−/− mice exhibit altered GI morphology and function, while Shank3B+/− mice exhibit a partial phenotype. These results indicate that Shank3, whose mutation is associated with ASD, is critical for function of the GI tract and its mutation may contribute to the etiology of GI comorbidities.